Mengoptimalkan Perkembangan Belajar Siswa melalui Penerapan Teori John Dewey dalam Pendidikan Agama Kristen - Arozatulo Telaumbanua; Asni Darmayanti Duha (Sekolah Tinggi Teologi Sumatera Utara, 2025)
This paper highlights the problems that occur in the development of student learning, which are influenced by several factors, namely the inability of Christian religious teachers to design Christian religious education learning that is taught to students, rigid learning methods and materials, and the environment and limitations of students in various aspects such as intellectual, genetic, social, cultural and physical. This paper uses a library research method with the main reference being John Dewey's book entitled